Exploring Tashbīh in Imruʾ al-Qays's Classical Poetry: A Comparative Study of Qifā Nabki and Liman Ṭalalun through the Lens of ʿIlm al-Bayān - Ali Lutpiana; Edi Komarudin; Mohammad Rosyid Ridho (Dzil Majaz: Journal of Arabic Literature, 2026)
Research on tasybih (simile) in Arabic literature has predominantly focused on modern literary works, while the characteristics of tasybih in classical Arabic poetry, particularly the Mu‘allaqāt of Imruʾ al-Qays, remain underexplored. This study aims to identify the types, purposes, and dominant patterns of tasybih in two qaṣidahs by Imruʾ al-Qays, namely Qifā Nabki Min Dhikrā Ḥabībin wa Manzili and Liman Ṭalalun Bayna al-Judayyati wa al-Jabali, from the perspective of ʿilm al-bayān. This research employed a descriptive qualitative approach using observation and note-taking techniques. The data consisted of poetic verses containing tasybih, which were analyzed by identifying the elements of tasybih, classifying its types based on the theory of Ali al-Jarim and Mustafa Amin, and examining their rhetorical purposes. The findings reveal 14 instances of tasybih, comprising eight instances in Qifā Nabki Min Dhikrā Ḥabībin wa Manzili and six instances in Liman Ṭalalun Bayna al-Judayyati wa al-Jabali. The dominant type is tasybih mursal mujmal, while the most frequent rhetorical purpose is tazyīn al-musyabbah (embellishing the subject of comparison). Furthermore, the objects of comparison are predominantly drawn from the natural environment and the daily life of pre-Islamic Arab society, creating vivid visual imagery, strengthening emotional expression, and enhancing the aesthetic quality of the poems. This study contributes by mapping the dominant patterns of tasybih, identifying its rhetorical tendencies, and describing the characteristics of comparative imagery in Imruʾ al-Qays's Jahiliyyah poetry, thereby enriching the study of ʿilm al-bayān and the stylistics of classical Arabic literature.